Development and Evaluation of Mouth Dissolving Films of Sumatriptan Succinate for Better Therapeutic Efficacy - Buchi N. Nalluri, B. Sravani, V Saisri Anusha, R. Sribramhini, K.M. Maheswari (Journal of Applied Pharmaceutical Science, 2013)
The present investigation was undertaken with an objective of formulating mouth dissolving films (MDFs) of an anti-migraine drug, Sumatriptan Succinate (SUM) to enhance convenience and compliance to the elderly and pediatric patients for better therapeutic efficacy. Film former, Hydroxy Propyl Methyl Cellulose along with film modifier/solubilizing agents, Polyvinyl pyrrolidone K30 (PVP K30) and Sodium Lauryl Sulphate (SLS) were used to formulate MDFs. The MDFs were prepared by wet film applicator technique and were evaluated for in vitro dissolution characteristics, in vitro disintegration time, and their physico-mechanical properties. MDFs with 13% (w/w) of HPMC E5 gave better dissolution properties when compared to HPMC E15. MDFs with PVP K30 and SLS gave superior dissolution properties when compared to MDFs without PVP K30 and SLS. The dissolution properties of MDFs with PVP K30 were superior when compared to MDFs with SLS. Overall, SUM MDFs showed good mechanical properties like tensile strength, folding endurance and % elongation and dissolution properties. These results suggest that the HPMC is an excellent film former which gives rapid drug release.
Keywords: Sumatriptan Succinate, Mouth Dissolving Films, HPMC,